Enhanced Long-term Stability and Carbon Resistance of Ni/MnxOy-Al2O3 Catalyst in Near-equilibrium CO2 Reforming of Methane for Syngas Production - Baya Djebarri; Fouzia Touahra; Nadia Aider; Ferroudja Bali; Moussa Sehailia; Redouane Chebout; Khaldoun Bachari; Djamila Halliche (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
Herein we study the catalytic activity/stability of a new generation of cheap and readily available Ni and Al-based catalysts using two Mn precursors, namely Mn(NO3)2 and Mn(EDTA)2- complex in the reaction of CO2 reforming of methane. In this respect, Ni/Al2O3 and two types of Ni/MnxOy-Al2O3 catalysts were successfully synthesized and characterized using various analytical techniques: TGA, ICP, XRD, BET, FTIR, TPR-H2, SEM-EDX, TEM, XPS and TPO-O2. Utilization of Mn(EDTA)2- as synthetic precursor successfully furnished Ni/Al2O3-MnxOyY (Y = EDTA) catalyst which was more active during CO2 reforming of methane when compared to Ni/MnxOy-Al2O3 catalyst, synthesized using Mn(NO3)2 precursor. Compared to Ni/MnxOy-Al2O3, Ni/Al2O3-MnxOyY catalyst afforded near-equilibrium conversion values at 700 °C (ca. 95% conversion for CH4 and CO2, and H2/CO = 0.99 over 50 h reaction time). Also, Ni/Al2O3-MnxOyY showed more resistance to carbon formation and sintering; interestingly, after 50 h reaction time, the size of Ni0 particles in Ni/MnxOy-Al2O3 almost doubled while that of Ni/Al2O3-MnxOyY remained unchanged. The elevated conversion of CO2 and CH4 in conjunction with the observed low carbon deposition on the surface of our best catalyst (Ni/Al2O3-MnxOyY) indicated the presence of MnxOy oxide positioning mediated simultaneous in-situ carbon elimination with subsequent generation of oxygen vacant sites on the surface for more CO2 adsorption. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).Corrigendum to this article is here: https://doi.org/10.9767/bcrec.15.3.9855.907-907